Grant writing: Moving from generating ideas to applying to grants that matter. (May 2017) - Nelson, David; Ruffalo, Leslie
There is an extraordinary burden placed upon the healthcare system and people as a result of health disparities that exist within the United States. If there is going to be a concerted effort to develop innovative strategies to reduce health disparities, input from the community and behavioral scientists can and should be included in this approach and narrative. Grant writing provides one vehicle to express the narrative and to provide a means to fund research and programs within clinic-based and community settings. This paper describes a four-step inquiry process to guide healthcare professionals with varying degrees of clinical and scholarship interests through the grant writing process. They include: (1) Why write grants (motivations), (2) what is the area of focus? (Interests), (3) whom should be on the project? (partnerships), and (4) what needs to happen next to move the idea forward? (actions) The complexity of psychosocial issues means that behavioral science is well suited to develop both hypotheses-driven and phenomenological research to understand bio-psycho-social health issues. Grant writing does not need to be mysterious or daunting. It can provide a means to an end, not only to fund research but also as a means to an end of health disparities.